2015
DOI: 10.1007/s11356-015-5809-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garlic and diallyl trisulfide on the growth, photosynthesis, and alkaline phosphatase activity of the toxic cyanobacterium Microcystis aeruginosa

Abstract: To identify a botanical algicide and elucidate the response of cyanobacteria to the extract from higher plants, the effects of garlic and garlic-derived diallyl trisulfide on Microcystis aeruginosa were studied. Effects were evaluated by changes in cell density, chlorophyll a, maximum effective quantum yield (Fv/Fm), effective quantum yield (YII), non-photochemical quenching (NPQ), and rapid light curves of M. aeruginosa. In addition, alkaline phosphatase activity (APA) was measured when M. aeruginosa was incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…It is thought that a primary method of impairing cyanobacteria growth by algaecide is by impairing the photosynthetic system of phytoplankton [ 14 , 32 ], although this mechanism has yet to be fully understood. Chlorophyll fluorescence has proven to be a useful tool for studying the behavior of PSII as it is a powerful, non-invasive, and reliable method [ 6 , 31 , 33 ]. As the fluorescence transient reflects the state of the primary bound plastoquinone, the secondary bound plastoquinone, the fluxes of photons, excitons, and electrons, the fast fluorescence curves were determined to show the changes of fluorescence intensity and relative variable fluorescence parameters [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is thought that a primary method of impairing cyanobacteria growth by algaecide is by impairing the photosynthetic system of phytoplankton [ 14 , 32 ], although this mechanism has yet to be fully understood. Chlorophyll fluorescence has proven to be a useful tool for studying the behavior of PSII as it is a powerful, non-invasive, and reliable method [ 6 , 31 , 33 ]. As the fluorescence transient reflects the state of the primary bound plastoquinone, the secondary bound plastoquinone, the fluxes of photons, excitons, and electrons, the fast fluorescence curves were determined to show the changes of fluorescence intensity and relative variable fluorescence parameters [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of alkaline phosphatase in phytoplankton have been studied in recent years. It has been proposed that, cyanobacteria can overcome conditions of serious phosphorous depletion by alkaline phosphorous production [ 6 , 39 , 41 , 43 ]. In the present study, we found that dihydroartemisinin and artemether could both inhibit the extracellular APA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations